2008
DOI: 10.1597/06-181.1
|View full text |Cite
|
Sign up to set email alerts
|

Subglossopalatal Synechia in Association with Cardiac and Digital Anomalies

Abstract: A 1-day-old boy in respiratory distress had a midline soft tissue band between the floor of the mouth and the posterior edge of the hard palate. There was also a soft palatal cleft, cardiac anomalies, and a hypoplastic right fifth finger and toe. Although his airway initially improved following urgent excision of the subglossopalatal band, he continued to have episodic desaturations. A tongue–lip adhesion opened his airway, and he subsequently underwent resection of juxtaductal aortic coarctation and ligation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Subglossopalatal membrane is a rare congenital oral synechia. It has been described in the literature only a handful of times 1–8 since Nakajima et al 1 first defined it in 1979 (Supplementary Digital Content, Table 1, http://links.lww.com/SCS/D433). Delineation between SGPM and BPM remnants based on embryologic anatomy and associated anomalies have been proposed 2,9 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subglossopalatal membrane is a rare congenital oral synechia. It has been described in the literature only a handful of times 1–8 since Nakajima et al 1 first defined it in 1979 (Supplementary Digital Content, Table 1, http://links.lww.com/SCS/D433). Delineation between SGPM and BPM remnants based on embryologic anatomy and associated anomalies have been proposed 2,9 …”
Section: Discussionmentioning
confidence: 99%
“…It was first described in the literature by Nakajima et al 1 The etiology is unknown, and whereas it has been categorized as a buccopharyngeal membrane (BPM) remnant, Zalzal et al 2 suggests that it may be due to an abnormal fusion event in the 6th or 7th week of gestation. Eight cases in the literature describe subglossopalatal membranes, [1][2][3][4][5][6][7][8] with 5 of them being associated with additional congenital anomalies (Supplementary Digital Content, Table 1, http://links.lww.com/ SCS/D433). Here, we present a case of subglossopalatal membrane with associated anomalies that was treated with surgical excision.…”
mentioning
confidence: 99%
“…Of the cases reviewed, only seven were medially located, and 11 were singular cordlike adhesions, as opposed to multiple adhesions. Midline subglossopalatal synechia has also been described in conjunction with cardiac and digital anomalies, representing a manifestation of oromandibular-limb hypogenesis spectrum (Oh et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Donepudi et al reported two cases of cleft palate lateral synechia (CPLS) syndrome in a single family and described surgical management of the synechia [13]. Albert K. Oh reported subglossopalatal synechia in association with cardiac and digital anomalies [14]. Snijman et al reported congenital fusion of gums in a 3 week old child along with temporomandibular joint ankylosis [15].…”
Section: Discussionmentioning
confidence: 99%